Improving Gross Motor Skills in Infants Aged 6-12 Months Through Infant Massage - Levi Tina Sari; Ita Noviasari; Ajeng Mahardika (Dewan Pimpinan Daerah Persatuan Perawat Nasional Indonesia Kota Blitar, 2026)
Background: Baby massage is a non-pharmacological intervention that can help accelerate growth and development stimulation in infancy. Suboptimal gross motor development can increase the risk of developmental delays and motor coordination disorders in the future. Objective: This study aims to determine the effect of baby massage on improving gross motor development in babies aged 6–12 months at Ohana Baby Spa Ngunut Tulungagung . Methods: This study used a quantitative design with a pre-experimental one-group pretest-posttest design. The population in this study was all babies who visited Ohana Baby Spa, with a sample of 35 respondents taken using the purposive sampling technique. Gross motor development was measured using the Pre-Screening Development Questionnaire (KPSP) observation sheet before and after the infant massage intervention . Results: The results of the study showed that before the intervention, most respondents were in the doubtful category (score 7–8), namely 54.3%, while after being given the intervention for two weeks, the majority of respondents increased to the appropriate category (score 9–10), namely 62.9%. Data analysis using the Wilcoxon Signed Rank Test obtained a z value = -5.444 with a p value = 0.000 (p < 0.05) which indicates a significant effect of infant massage on gross motor development. Conclusion: Baby massage is effective in helping stimulate gross motor skills in babies aged 6–12 months. Therefore, baby massage can be recommended as part of routine stimulation care to support optimal growth and prevent developmental delays in babies.